Mitochondria Endoplasmic Reticulum Contact Sites (MERCs): Proximity Ligation Assay as a Tool to Study Organelle Interaction - Benhammouda, Sara; Vishwakarma, Anjali; Gatti, Priya; Germain, Marc (Frontiers in Cell and Developmental Biology, 2021)
Organelles cooperate with each other to regulate vital cellular homoeostatic functions. This occurs through the formation of close connections through membrane contact sites. Mitochondria-Endoplasmic-Reticulum (ER) contact sites (MERCS) are one of such contact sites that regulate numerous biological processes by controlling calcium and metabolic homeostasis. However, the extent to which contact sites shape cellular biology and the underlying mechanisms remain to be fully elucidated. A number of biochemical and imaging approaches have been established to address these questions, resulting in the identification of a number of molecular tethers between mitochondria and the ER. Among these techniques, fluorescence-based imaging is widely used, including analysing signal overlap between two organelles and more selective techniques such as in-situ proximity ligation assay (PLA). While these two techniques allow the detection of endogenous proteins, preventing some problems associated with techniques relying on overexpression (FRET, split fluorescence probes), they come with their own issues. In addition, proper image analysis is required to minimise potential artefacts associated with these methods. In this review, we discuss the protocols and outline the limitations of fluorescence-based approaches used to assess MERCs using endogenous proteins.